Analysis of the City Bus Service Network in Bogor City (Case Study: Bubulak Terminal - Cidangiang Route) - Syaiful, Syaiful; Damiana, Salma Leandra; Prayudyanto, Muhamad Nanang (Universitas Ibn Khaldun Bogor, 2024)
BisKita Trans Pakuan Bogor Corridor 1 route line Bubulak Terminal - Cidangaing is expected to reduce the number of city transportation and private vehicles as an effort to overcome congestion in Bogor City. An assessment is needed to determine whether the service and operational performance of the bus are up to standard. The indicators used in the evaluation of operational performance refer to the Decree of the Director General of Land Transportation SK.687/AJ.206/DRJD/2002 and the world bank, while the minimum service standards refer to the Minister of Transportation Regulation No. 10 of 2012 and Minister of Transportation Regulation No. 27 of 2015. This study aims to determine the performance level of the facilities and infrastructure of BiskKita Trans Pakuan Corridor 1 services. This research uses quantitative methods. The results showed; the average load factor on the departure route during the weekday has met the standard value of 74% and on the return route has not met the standard of 66% while the passenger load factor on the departure and return routes during the weekend is 50% and 49% which means it has not met the standard, the average headway during the weekday has met the standard of 9.40 minutes and during the weekend has not met the standard of 12.90 minutes, the average frequency during the weekday and weekend has met the standard of 6 bus/hour and 4 bus/hour, The average return and departure travel times have met the standards of 35,59 minutes and 54.10 minutes during the weekday and 40.67 minutes and 58.00 minutes during the weekend, the average return and departure speeds have met the standards of 23.59 km/hour and 22.81 km/hour during the weekday and 22.41 km/hour and 21.94 km/hour minutes during the weekend, the average fleet operating during the weekday and weekend has met the standards of 100% and 92% of the total fleet. Based on the results of the analysis, some indicators of the operational performance of BiskKita Trans Pakuan Corridor 1 have not met the standards because some of the load factors are still below the standard.